2018
DOI: 10.1186/s13578-018-0247-x
|View full text |Cite
|
Sign up to set email alerts
|

TIPE2 acts as a biomarker for tumor aggressiveness and suppresses cell invasiveness in papillary thyroid cancer (PTC)

Abstract: BackgroundTumor necrosis factor (TNF)-alpha-induced protein 8-like 2 (TIPE2 or TNFAIP8L2) is a newly described negative immune regulator and is closely associated with various tumors. However, the expression and roles of TIPE2 in PTC is unknown.ResultsIn the present study, TIPE2 upregulation in PTC tissues was found to be negatively associated with tumor size, capsule infiltration, peripheral infiltration and tumor T stage, which could be used to predict tumor invasiveness. TIPE2 overexpression significantly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Ten high-power fields were randomly selected from each specimen to observe and record the percentage of positively stained cells of TIPE2 in tumor cells (0: 0%; 1: 1∼25%; 2: 26∼50%; 3: 51∼75%; 4: 76∼100%) and the corresponding staining intensity (0: no staining; 1: light yellow; 2. Medium tan; 3: dark tan) [ 15 ]. The expression score of TIPE2 was obtained by multiplying the results of the above two scores, which ranged from 0 to 12 points.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten high-power fields were randomly selected from each specimen to observe and record the percentage of positively stained cells of TIPE2 in tumor cells (0: 0%; 1: 1∼25%; 2: 26∼50%; 3: 51∼75%; 4: 76∼100%) and the corresponding staining intensity (0: no staining; 1: light yellow; 2. Medium tan; 3: dark tan) [ 15 ]. The expression score of TIPE2 was obtained by multiplying the results of the above two scores, which ranged from 0 to 12 points.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent studies have found that TIPE2 is also involved in multiple signaling pathways of tumorigenesis and development, and plays a key role in different processes of cancer cell survival, proliferation, migration and invasion [ 6 , 7 ]. Among different cancer types, TIPE2 expression level was decreased in liver cancer [ 8 ], small cell lung cancer [ 9 ], stomach cancer [ 10 ], esophageal cancer [ 11 ] and prostate cancer [ 12 ], and increased in kidney cancer [ 13 ], colon cancer [ 14 ] and thyroid papillary carcinoma [ 15 ]. TIPE2 has shown its potential as a novel tumor therapeutic target and biomarker in various cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have shown that the expression of TIPE2 was positively correlated with the Tumor Node Metastasis (TNM) staging in renal cell carcinoma and lymph node metastasis of colon cancer (Zhang et al, 2013). Further, a high expression of TIPE2 was negatively correlated with tumor size, envelope infiltration, peripheral infiltration, and tumor T-stage in thyroid adenocarcinoma (Jia et al, 2018). TIPE2 was more expressed in early-stage tumor tissues than in advancedstage tumor tissues in pancreatic ductal adenocarcinoma (PDAC) (Sun et al, 2021).…”
Section: Tipe Family Structuresmentioning
confidence: 99%
“…In the study of papillary thyroid carcinoma (PTC), TIPE2 overexpression was observed in tumor samples, and inhibited viability, proliferation, and invasion of PTC cells. Furthermore, TIPE2 attenuated tumor invasiveness via inhibition of Rac1, resulting in reduced MMP-9 and uPA expression, indicating its crucial role in predicting tumor aggressiveness of PTC 76 ( Table 1 ). In Non-Hodgkin’s lymphoma (NHL), the increased expression of TIPE2 was identified in both peripheral T cell lymphoma and diffuse large B-cell lymphoma (DLBCL), and TIPE2 expression in DLBCL was stronger than that in T lymphoma.…”
Section: Roles Of Tipe2 In Cancersmentioning
confidence: 99%